The impact of metacognitive beliefs in young and old adults’ memory (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The present study aims to understand the processes related to how good one’s memory is (along with its self-efficacy) and the actual memory performance throughout human development, as well as false memories’ production (i.e., remembering events that did not actually occur). The experiment was conducted with 82 young adult participants, with ages ranging from 30 to 35 years, and 79 old adult participants, with ages ranging from 65 and 70 years. We used the Brazilian version of the word associate procedure (with neutral and emotional words) followed by a recognition test to assess memory performance and the metacognitive beliefs questionnaire to evaluate memory beliefs for the words of the test. Results indicate that the more young adults believe in their memory, the fewer false memories were produced for neutral information.
Keywords: metacognition; memory; false memory; aging